Analysis of the effect of using divalent and trivalent iron compounds on sludge dewatering performance in thickening units - Ebrahim Alamatian; Bojan Đurin; Sara Dadar; Domagoj Nakić (Water Practice and Technology, 2023)
Sludge is one of the by-products of wastewater treatment plants (WWTPs). To assist biological processes, part of the produced sludge is returned to the treatment process and the excess is removed from the treatment plant whereby it undergoes thickening and dewatering. Numerous studies have been conducted to investigate the effect of different coagulants on dewatering from sludge, but the effect of using divalent iron for this purpose has not been investigated so far. In this research, the effect of divalent and trivalent iron compounds (ferrous sulfate and ferric chloride) on the dewatering of excess sludge of the first module of the Bojnourd WWTP (Iran) has been investigated. In this regard, first, the effect of different doses of each coagulant to optimize the dewatering characteristics of sludge was investigated and then the effect of pH change by adding lime was investigated. The results showed that the addition of optimal doses of FeSO4 (0.6 and 0.4 g/l) and lime (0.664 and 1.5866 g/l) reduced the capillary suction time of sludge by 30.6 and 32.7%, respectively, while reducing the moisture content of sludge cake by 26 and 30.6%. HIGHLIGHTS A novel methodology of sludge technology.; First implementation of the new materials for sludge dewatering.;